Case Report: Infra-Low-Frequency Neurofeedback for PTSD: A Therapist's Perspective - Spreyermann, Regula (Frontiers in Human Neuroscience, 2022)
This article describes the practical use of a combination of trauma psychotherapy and Neurofeedback (ILF Neurofeedback and Alpha-Theta training) for the treatment of patients diagnosed with complex posttraumatic stress disorder (C-PTSD). The indication for this combined treatment is the persistence of symptoms of a hyperaroused state, anxiety and sleep disorders alongside with an adequate trauma-focused psychotherapy and supporting medication as recommended in the Guidelines of the German Society of Psychotraumatology (DeGPT) . Another indication for a supplementary treatment with Neurofeedback is the persistence of dissociative symptoms. And last but not least the Neurofeedback treatment after a trauma-focused Psychotherapy session does help to calm the trauma-related reactions and process the memories. The setting and the process of the combined therapy is shown, the complex situation and the development under therapy is illustrated using two case reports. Overall a rather satisfying result of this out-patient treatment program can be seen in the qualitative appraisal overlooking 7 years of practical application.